The Exogenous Shock of General Elections: Politically Connected Firms and Stock Price Crash Risk - Wai-Yan Wong; Chai-Aun Ooi; Chee-Wooi Hooy (International Journal of Business and Society, 2022)
Malaysia experienced unusual political turmoil during the general elections in 2008 (GE 2008) and 2013 (GE 2013). This study examines how such exogenous political shocks affect the stock price crash risk of politically connected firms (PCFs) compared to non-PCFs in Malaysia. The data for this study covers from the year 2002 to 2017. A balanced panel of 529 firms from 2002-2017 is used for analysis. This study finds that PCFs display a significantly lower stock price crash risk after GE 2008 and GE 2013 but not before GE 2008. However, the results are only applicable to the PCFs through the politically connected board of directors and businessmen. Further analysis reveals that increasing foreign (government) strategic free float shareholdings result in lower stock price crash risk of PCFs through the politically connected board of directors (government direct shareholdings). Our results provide several perspectives on the connection between stock price crash risk and political stability.